Bioelectrical impedance in the assessment of nutritional status - Ręba, Patrycja (Journal of Education, Health and Sport, 2020)
Introduction Bioelectrical impedance analysis is based on the difference in electric conduction in the water and fat environment. Adipose tissue and extracellular water are devoid of capacitive resistance (reactance), whereas they show passive electrical resistance (resistance). The current frequencies used in the bioelectrical impedance test do not affect nerve or heart muscle irritation. The current is completely safe and practically imperceptible to the patient. Aim The purpose of the work is to analyze bioelectrical impedance in assessing nutritional status. Material and method Review of available literature on the subject. Results Impedance is a category of electrical resistance consisting of two elements: resistance (passive electrical resistance) and reactance (capacitive, active electrical resistance). Resistance refers to the specific resistance of individual tissues. It is proportional to the voltage and inversely proportional to the total water content in the body. Reactance is associated with the electrical capacity of cell membranes that act as capacitors. The phase angle is a parameter that illustrates the circulation of water between the intracellular and extracellular space. Provides information on cell membrane integrity, cell health and total body mobility. BCM changes are typical for some chronic diseases, such as AIDS or cancer. Subjective global nutrition assessment (SGA) is the gold standard for determining nutritional status. Conclusions The phase angle value allows you to track the nutrition of the body as well as monitor recovery and physical fitness. Keeping BCM at the right level has a positive effect on your health. Maintaining BCM is a major goal in all types of nutrition therapies. FFMI allows observation of the effects of treatment, disease or aging patients.